Cervical Pessary Placement for Prevention of Preterm Birth in Unselected Twin Pregnancies: A Randomized Controlled Trial. Issue 4 (December 2016) - Nicolaides, K.H.; Syngelaki, A.; Poon, L.C.; De Paco Matallana, C.; Plasencia, W.; Molina, F.S.; Picciarelli, G.; Tul, N.; Celik, E.; Lau, T.K.; Conturso, R.
Abstract : ( Am J Obstet Gynecol . 2016;214:3.e1–e.9) Preterm birth is responsible for >70% of all neonatal and infant deaths. Twins, with a prevalence of 1.5% of pregnancies, account for about 25% of preterm births. Randomized controlled trials in singleton pregnancies with short cervical length reported that the prophylactic use of progesterone reduced significantly the rate of preterm birth and neonatal morbidity. In twin pregnancies, progestogens and cervical cerclage have been shown to be ineffective in reducing preterm birth. The aim of this multicenter Randomized controlled trial was to test the hypothesis that the insertion of a cervical pessary in twin pregnancies, compared with expectant management, would reduce the rate of spontaneous birth at <34 weeks' gestation.